2021
DOI: 10.1161/strokeaha.120.033431
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Fibroblast-Like Cells in Stroke and Other Neurological Disorders

Abstract: Fibroblasts are the most common cell type of connective tissues. In the central nervous system (CNS), fibroblast-like cells are mainly located in the meninges and perivascular Virchow-Robin space. The origins of these fibroblast-like cells and their functions in both CNS development and pathological conditions remain largely unknown. In this review, we first introduce the anatomic location and molecular markers of CNS fibroblast-like cells. Next, the functions of fibroblast-like cells in CNS development and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Classical spinal cord glial scars also contain fibroblasts that originate from meninges, choroid plexus, and perivascular spaces ( Dorrier et al, 2021 ; Silver and Miller, 2004 ; Xu and Yao, 2021 ). In the rat DFP study, no trauma was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Classical spinal cord glial scars also contain fibroblasts that originate from meninges, choroid plexus, and perivascular spaces ( Dorrier et al, 2021 ; Silver and Miller, 2004 ; Xu and Yao, 2021 ). In the rat DFP study, no trauma was involved.…”
Section: Discussionmentioning
confidence: 99%
“…CNS fibroblasts include meningeal fibroblasts and perivascular fibroblasts, which are located in all three layers of the meninges (pia, arachnoid, and dura) and perivascular space, respectively. 136,137 Under physiological conditions, perivascular fibroblasts are sandwiched between vSMCs and astrocytic endfeet in large blood vessels. 38,136 Our unpublished data showed that fibroblasts were associated with small blood vessels after hemorrhagic stroke, suggesting a possible role of fibroblasts in BBB regulation under pathological conditions.…”
Section: Expression and Functions Of Laminin And Its Receptors In The...mentioning
confidence: 99%
“…136,137 Under physiological conditions, perivascular fibroblasts are sandwiched between vSMCs and astrocytic endfeet in large blood vessels. 38,136 Our unpublished data showed that fibroblasts were associated with small blood vessels after hemorrhagic stroke, suggesting a possible role of fibroblasts in BBB regulation under pathological conditions.…”
Section: Expression and Functions Of Laminin And Its Receptors In The...mentioning
confidence: 99%
“…Fibroblast-like cells are common in the connective tissue of peripheral organs (Xu and Yao 2021 ). Within the CNS their location is mostly restricted to the basal laminae of the vascular system (Soderblom et al 2013 ).…”
Section: The Pathobiology Of the Glial Scarmentioning
confidence: 99%